Circular Dichroism of Amino Acids: Following the Structural Formation of Phenylalanine. - Amdursky,N; Stevens,MM (Chemphyschem, 2015)
Circular dichroism (CD) is frequently used to assess the secondary structure of peptides and proteins, whereas less attention has been given to their building blocks, that is, single amino acids, as they do not possess a secondary structure. Here, we follow the CD signal of amino acids and reveal that several acids exhibit a unique CD pattern as a function of their concentration. Accordingly, we propose an eight-level classification of the CD signal of the various amino acids. Special focus is given to the CD pattern of phenylalanine (Phe), for which we observe the formation of an ultra-narrow CD peak (full width at high maximum of only 5nm). This CD peak can be attributed to the formation of Phe-based chiral structural features. Further support for the formation of an ordered structure is given by using NMR, and the additional self-assembly process of Phe to tubular structures.